Examination of Islamic law of Inheritance [Miraath] in Kwara State Lower Courts - Muhammad Jumat Dasuki (Cyber Media Indonesia, 2022)
The Islamic law of Inheritance has been pre-ordained by Allah (S.W.T.) in a wise and gradual manner. It has determined the rulings and methods to distribute inheritance among all beneficiaries with the purpose to act fairly to all levels of beneficiaries and to avoid discrepancies among them. Among Muslims today internecine scramble for the distribution of the property of a deceased person has become a serious societal problem that requires profound attention. The struggle over inheritance of property has pitted children of the same father against each other. Conflicts among Muslims over inheritance have resulted in unrest in the society. It is observed that the crises sometimes arise because of issuance of wrong rulings by the Alfas called to distribute the estate or by Qaadis especially at juridical Courts of lower status. Therefore this work examines the application of Islamic inheritance system in Lower Courts of Kwara State by comparing and contrasting the methodologies applied by the individual Court in the study areas with the laid down Islamic principles of Islamic law of inheritance. It also appraises the correctness or otherwise of inheritance cases decided upon by the Area Courts in Kwara State. The paper applies analytical and historical approaches for this study as well as library sources as a tool of sourcing for information and concludes with useful recommendations.